ANALISIS KEBUTUHAN MODUL BERBASIS PERMAINAN EDUKATIF DI ERA 4.0 DENGAN MODEL DISCOVERY - Nurma Zuliyanti; Irfai Fathurohman; Sri Utaminingsih (Journal Prakarsa Paedagogia, 2021)
The purpose of this study was to analyze the need for educational game-based module development in the 4.0 era with a discovery model. This research is preliminary research from research and development (Research and Development). The design of this research is need analysis or survey research. The respondents of this study were students and teachers of grade VI at SDN 2 Kembang, SDN 1 Jinggotan, and SDN 2 Kembang Jepara. Data collection techniques through questionnaires and documentation. The results of needs analysis through questionnaires and documentation showed that, 1) limited teaching materials became an obstacle in the learning process, 2) 82% of teachers needed the development of an educational game-based module in the 4.0 era with discovery models, 3) 83% of students needed development an educational game in the era of 4.0 with a discovery model. Based on these results, it can be concluded that it is necessary to develop an educational game-based module in the 4.0 era with a discovery model to improve student learning outcomes.